Chemical cross‐linking facilitates antigen uptake and presentation and provides improved protection from Mpox with a dual‐antigen subunit vaccine - Long Chen; Chao Shang; Zihao Wang; Mengzhu Zheng; Cuiling Zhang; Dapeng Li; Zhanqun Yang; Yuchao Dong; Yuru Xu; Yunsheng Yuan; Shiyong Fan; Wu Zhong; et al. (MedComm)
Abstract Antigen uptake, processing, and presentation are crucial for the immune responses of protein‐based vaccines. Herein, we introduced a reversible chemical cross‐linking strategy to engineer protein antigens, which can be tracelessly removed upon antigen‐presenting cell (APC) uptake and cellular reduction. The chemically cross‐linked antigen proteins presented significantly enhanced uptake and epitope presentation by APC. We applied this strategy to monkeypox virus antigens A29L and A35R to construct dual‐antigen subunit vaccines. Our results revealed that chemical cross‐linking was robust enough to improve both proteins' APC uptake and lymph node accumulation, with each protein being chemically cross‐linked and administered separately. In vivo validation revealed that the chemical cross‐linking of the two antigen proteins improved immune responses, with increases in antigen‐specific antibody and live virus‐neutralizing antibody production. Monkeypox virus challenge experiments revealed that dual‐antigen vaccines prepared via the chemical cross‐linking strategy mitigated tissue damage, reduced the virus load, and extended mouse survival, which proved that the chemical cross‐linking strategy is valuable for protein‐based subunit vaccine development. In consideration of the current threats from the monkeypox virus and potential future emerging pathogens, the chemical cross‐linking strategy provide powerful tools.